EFFECT OF CRISIS ON BISNIS-27 MARKET PERFORMANCE (STUDY CASE OF PANDEMIC AND RUSSIAN WAR) - Wintang Tathyo Pradipto (Jurnal Ekonomi dan Bisnis (EK dan BI), 2023)
This study seeks to explore how the crisis caused by the pandemic and war can impact the return on the BISNIS-27 index in Indonesia. This study aims to explain how the effect of an increase in daily cases, war and other variables on stock returns. This research is a quantitative research employing secondary data. The data source for this research is the additional weekly cases of Covid 19 in Indonesia for 140 weeks in the period from 2020 to 2022 which were reported and collected via kawalcovid19.id, the BISNIS-27 price index obtained from yahoo finance. For the Russian-Ukrainian war variable, a dummy variable is used, 0 for the period before the war and 1 when the first Russian invasion broke out into Ukraine. The other variables that become control variables are the Oil Price (WTI), Gold Price (XAUUSD), Federal Funds Rate, Exchange Rate (USD-IDR) and Interest Rate (BI7DRR). The results obtained are that the Covid-19 pandemic has a significant negative effect on the rate of return on the BISNIS-27 index. The negative coefficient shows that each increase in daily cases will decrease the rate of return on the BISNIS-27 index. The Oil Price variable is not significant on thereturn on the BISNIS-27 index. The Gold Price variable is not significant to the rate of return for the BISNIS-27 index. The Foreign Interest Rate variable is not significant to the return for the Business 27 index. The Foreign Index Price variable (DJIA) is significant with a negative coefficient on the return of BISNIS-27 index. The negative coefficient indicates that any decrease in the DJIA index price will increase the BISNIS-27 index return rate. The Exchange Rate variable is significant with a positive coefficient on the Business-27 return rate. The positive coefficient shows that any strengthening of the exchange rate will increase the return on the BISNIS-27 index. The Interest Rate variable is significant with a negative coefficient on the BISNIS-27 index return. The negative coefficient indicates that any decrease in the interest rate will increase the rate of return on the BISNIS-27 index. The war variable is not significant to the return of BISNIS-27 index. In conclusion, the addition of daily cases of Covid 19 has a negative impact on the index return rate, this is in line with Liu's (Liu et al. 2020) research which states that stock markets in significantly affected countries and regions fell sharply following the virus outbreak. Comparatively speaking, Asian nations have seen more unfavorable abnormal returns. Zhang et al. (2020) using pairwise correlation in few countries states that a higher level of volatility and systematic risk are linked to COVID-19. Albulescu (2020), using US stock market from March 11, 2020 to May 15, 2020 with OLS regression states that higher financial volatility is related to the new confirmed case. For the war variable, the results are not significant, and until this research is completed, the Russian invasion of Ukraine has not over yet, so further research is needed to see the impact more accurately.